Understanding beliefs, teachers’ beliefs and their impact on the use of computer technology (2012)
This theoretical review addresses the construct of beliefs in education and English as a foreign language, and their impact when integrating technology. A thorough definition and categorization of teachers’ beliefs will be provided. In addition, studies conducted in various educational settings examining the effects of teachers’ beliefs and the use of technology will be reviewed. Additional information on models attempting to explain human behavior and the use of computers will be presented as well in order to discuss these research results in light of local efforts made to solve the gap of integrating technology through the Computadores para Educar Program in Colombian public schools. Este artículo gira en torno al concepto y la categorización de las creencias sobre la educación y la enseñanza del inglés como lengua extranjera, y se estudia cómo la tecnología incide en dichas creencias cuando esta se integra. Además de revisar varios estudios acerca de los efectos de dichascreencias respecto al uso de la tecnología, se presentan tanto los modelos investigativos y estudios que han intentando describir el comportamiento humano frente al uso de computadores como sus resultados. Estas investigaciones son relevantes para el programa Computadores para Educar,con el que se busca combatir la falta de acceso a la tecnología en Colombia, y beneficiar a los colegios públicos.